A responsabilização das empresas transnacionais por ofensas aos direitos humanos no Brasil - Cúnico, Fernando José (2023)
This dissertation aims to develop the theme of the condition of transnational companies as possible and real offenders of Human Rights, in the increase of their activities. Commonly, these large conglomerates carry out their activities without observing local laws, and judicial convictions are not uncommon. However, because they are transnational, their way of acting, structure and absence of goods at the site of damage, generates immense difficulty in receiving compensation by countries whose laws were not complied with. This hypothesis perfectly fits the situation of shielding the transnational company and the feeling of injustice towards the offended parties. In this way, seeking to analyze the national diplomas and, above all, the international ones, with regard to the effective reparation of the damage (whether in fact there is or not in the Brazilian system), when human rights are violated, this research concludes, through from the documentary analysis of judgments, legal texts, treaties and international conventions, in addition to national and international bibliography on the subject, and from the case study involving the native peoples of the Amazon, that Brazil is below what is expected in terms of civil reparation for the damage. For that, the hypothetical-deductive method was used, through the qualitative technique.